1996
DOI: 10.1097/00004714-199612000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Depressive Illness Does Fit an Exponential Model

Abstract: A very large number of therapeutic trials of antidepressant drugs have been reported in the scientific literature. Until now, the comparison of one drug with another, or with placebo, has been performed typically by comparing the scores on depression rating scales of the two groups of patients at fixed points of time after the beginning of therapy. It was postulated in 1989 that the curves of the recovery scores followed an exponential curve of the formula y = ae-bx + c. This hypothesis was tested in a double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…However, comparison with published data also supports our claim of the clinical relevance of our findings. Priest and co-workers [23] specify the upper limit of a¸normal range for the total score of the 17-item HAMD (when the scale is filled in for patients who do not suffer from depression) as approximately 10 points. At the end of the treatment program, the HAMD total score mean and median in the Hypericum group had fallen below this upper limit, which was not the case in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparison with published data also supports our claim of the clinical relevance of our findings. Priest and co-workers [23] specify the upper limit of a¸normal range for the total score of the 17-item HAMD (when the scale is filled in for patients who do not suffer from depression) as approximately 10 points. At the end of the treatment program, the HAMD total score mean and median in the Hypericum group had fallen below this upper limit, which was not the case in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Priest et al [23] and by Friede et al [9] has shown that the time course of the HAMD total score during recovery from depression can be described by fitting an exponential regression model to the data. While such models can describe the data actually observed during a trial, they may also be used to predict the future recovery process beyond the end of the period of observation.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…1). For example, it has been reported previously that the changes in depression rating scale scores over time for treated and control groups can be well fit with logarithmic curve [11]. More recently, the NEMESIS study from the Netherlands studied a community sample in which there were 250 new episodes of major depression.…”
Section: Global Improvementmentioning
confidence: 99%
“…Priest et al [2] proposed to fit an exponential model to the mean scores of the treatment groups by:…”
Section: Introductionmentioning
confidence: 99%
“…The constant ␤ 3 has to be specified in advance, because otherwise it is not possible to estimate the regression equation for y'(t) . Priest et al [2] proposed to choose arbitrarily ␤ 3 = 5, because different studies with active treatments have shown that the HAM-D is less than 10 after 6 weeks, due to some background of depressive symptoms even in the "healthy" population, and it is higher than 0 by definition of the HAM-D scale. Priest et al concluded to take an arbitrary value between 0 and 10 for the score after complete recovery.…”
Section: Introductionmentioning
confidence: 99%